Design, synthesis, docking, and antimicrobial evaluation of some novel pyrazolo[1,5-a]pyrimidines and their corresponding cycloalkane ring-fused derivatives as purine analogs - Abdallah AEM; Elgemeie GH (Dove Medical Press, 2018)
Amira EM Abdallah, Galal H Elgemeie Department of Chemistry, Faculty of Science, Helwan University, Helwan, Cairo, Egypt Background: Over the years, pyrazolopyrimidine derivatives have been recognized as having antimicrobial activities. Recently, we reported different synthetic methods to prepare pyrazolopyrimidine derivatives as anticancer and antimicrobial agents. The studies showed that our previously reported 5-aminopyrazoles 2 act as a building block for the preparation of a variety of interesting pyrazolopyrimidines as purine analogs. Purpose: The objective of this study was to describe the direct new method for preparation of novel pyrazolo[1,5-a]pyrimidine derivatives and their corresponding cycloalkane ring-fused derivatives. Also, the new compounds were tested in vitro for their antibacterial and antifungal activity properties. Methods: Pyrazolo[1,5-a]pyrimidine derivatives were prepared by the reaction of our previously reported 5-aminopyrazoles 2 with suitable sodium salts of (hydroxymethylene) cycloalkanones and sodium salts of unsaturated ketones. Results: The structures of the new compounds were characterized according to their mass spectroscopy, 1H NMR, IR and elemental analyses. Compounds 8b, 10e, 10i, and 10n were the most active compounds against Gram-positive and Gram-negative bacterial species. Compound 10i with two moieties of 4-Br-C6H4 revealed increased reactivity compared with ampicillin as standard reference. Conclusion: About twenty two novel pyrazolo[1,5-a]pyrimidine derivatives and their corresponding cycloalkane ring-fused derivatives were prepared through the reaction of 5-aminopyrazoles 2 with different sodium salts of (hydroxymethylene) cycloalkanones and sodium salts of unsaturated ketones. The antibacterial and antifungal activities of the newly synthesized compounds were evaluated and revealed that compounds 8b, 10e, 10i, and 10n were the most active compounds against Gram-positive and Gram-negative bacterial strains. Keywords: pyrazolo[1,5-a]pyrimidines, 5-aminopyrazoles, 2-(hydroxymethylene)-1-cycloalkanones, 2-formylcycloalkanones, antibacterial, antifungal, docking studies